Analisis Penilaian Dan Minat Beli Produk Sepeda Motor Yamaha dikalangan Mahasiswa - Naoval hakiki rd; Betha M Zaky; Syamsul Hidayat (Jurnal Kajian dan Penelitian Umum, 2024)
This study aims to analyse the variables of price perception and product quality. This type of research is descriptive verification research with a sample size of 54 people. Based on the research results obtained that simultaneously the purchase intention variable is significantly influenced by the variables of price perception and product quality. This means that the better the price perception, product quality and lifestyle, the more consumer buying interest in Yamaha in Regency will increase. Partially, the price perception variable has a significant effect on the purchase intention variable. Partially, the product quality variable has a significant effect on the purchase intention variable.